Modeling positive inter-jurisdictional public spending spillovers - Martin Gregor (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper builds spatial microfoundations for the functional forms used in the analysis of inter-jurisdictional public spending spillovers. It introduces a symmetric bilateral model that distinguishes between three stages: production of multiple public inputs (intermediary goods), production of multiple public outputs (final goods) including asymmetries and non-additive aggregations, and consumption of the public outputs with asymmetries and preferences for variety. The model is characterized by seven modeling features, and the paper demonstrates how these features are combined in the relevant literature. The paper identifies sufficient conditions for the different combinations of the features to be isomorphic. Additionally, it analyzes which microfoundations for the inter-jurisdictional spillovers lead to asymmetrically structured demands for public spending.
Keywords: H4; H7; 330; spillover; externality; complementarity; weak-link; local public goods